ZH-1 enhances the anticancer activity of gemcitabine via deoxyribonucleotide synthesis and apoptotic pathway against A549 cells. (September 2018) - Guo, Jianru; Li, Yan; Lam, Christopher Wai Kei; Wang, Caiyun; Yao, Meicun; Zhang, Wei
Abstract: The purpose of this study was to investigate the inhibitory effect of ZH-1 ((6S, 9aS, 6aR, 9bR)-6-(phenylcarbonyl)-6, 6a, 9a, 9b-tetrahydro-8H-azolidino[3, 4-a]b enzo [e]indolizine-7, 9-dione) and its potential interaction with gemcitabine in A549 cells. MTT assay showed that the combined use of gemcitabine and ZH-1 presented a significant inhibition effect on A549 cell growth with the cell viability from 82.3 ± 5.6% to 51.0 ± 6.6%. The CI value was 0.60 suggesting a synergistic effect between these two drugs. HPLC-MS/MS data indicated that combined treatment with gemcitabine and ZH-1 induced a significant decrease in deoxyadenosine triphosphate, deoxycytidine triphosphate, deoxyguanosine triphosphate and deoxythymidine triphosphate levels compared with use of gemcitabine alone. Five RNs as well as seven dRNs were considered to be significantly contributive to the discrimination of samples. Furthermore, western blot analysis revealed that the combination treatment caused A549 cell apoptosis via the intrinsic pathway by up-regulating Bax/Bcl-2 ratio, activating caspase-9, caspase-3 and poly-ADP-ribose polymerase, and promoting caspase-7, caspase-9 and poly-ADP-ribose polymerase cleavage. Collectively, the combined treatment with gemcitabine and ZH-1 exerted a strong synergistic action on anticancer activity through growth inhibition, perturbations in ribonucleotides and deoxyribonucleotides and the activation of intrinsic apoptotic signaling pathway. Highlights: The inhibitory effect of ZH-1 and its potential interactions with gemcitabine in A549 cells was investigated. The combined treatment of gemcitabine and ZH-1 on the levels of ribonucleotides and deoxyribonucleotides was demonstrated. The combined use of gemcitabine and ZH-1 in A549 cells enhanced induction of apoptosis via the intrinsic pathway.